Pengaruh Konsentrasi Etanol Dan Waktu Ekstraksi Menggunakan Metode Microwave Assisted Extraction (MAE) Terhadap Aktivitas Antioksidan Ekstrak Daun Murbei (Morus alba L.) - Putri, Kadek Diah Ary; Yusasrini, Ni Luh Ari; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPADO - 10.24843/itepa.2025.v14.i02.p02, 2025)
Mulberry leaves ( Morus alba L.) contained bioactive components such as phenolic, flavonoids, and tannins, that fuction as antioxidants. These bioactive components can be acquired through an extraction procedure. Concentration of ethanol and extraction time can influenced the bioactive compounds in mulberry leaf extract. Extraction can be performed using various methods, including Microwave Assisted Extraction (MAE). This study aimed to assess the impact of ethanolx concentration and extractionftime using the MAE method on antioxidant activity and identify the optimum antioxidant activity. The research design was randomised factorial consisting of 2 factors. Ethanol concentration (50%, 60%, 70%, 80% ethanol) was the first factor, and extraction duration (3, 5, 7, and 10 minutes) was the second factor. All treatments were repeated twice, resulting in 32 research units. To identify significant differences, analysis of variance and Duncan's Multiple Range Test (DMRT) were used to examine the data. The results of the mulberry leaf extract indicated that 70% ethanol for seven minutes was the best treatment for mulberry leaf extraction using the MAE method yielding 12.97%, with a total phenolic content of 138.19 ± 3.41 mg GAE/g, total flavonoid content of 58.45 ± 0.32 mg QE/g, total tannin content of 20.18 ± 0.18 mg TAE/g, and IC 50 value of 38.44 ± 0.94 ppm. Keywords: Antioxsidants, bioactive compound, mulberry leaves,  Microwave Assisted Extraction